2004
DOI: 10.1111/j.1365-2249.2004.02634.x
|View full text |Cite
|
Sign up to set email alerts
|

L-ficolin in children with recurrent respiratory infections

Abstract: SUMMARYThe lectin pathway of complement activation is used by a collectin, mannan-binding lectin (MBL), and two ficolins, L-ficolin and H-ficolin, to opsonize microorganisms for phagocytosis. We published evidence recently that MBL insufficiency is associated with recurrent respiratory infections in childhood. We have now measured serum L-ficolin in 313 respiratory infection patients and 74 healthy control children. L-ficolin concentrations below the lower limit of the control group were found in 6% of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 21 publications
4
46
0
1
Order By: Relevance
“…In a cohort of Polish children with recurrent respiratory tract infection, a group of patients with underlying atopic disorder were significantly more likely to have L-ficolin levels less than the lower range seen in healthy controls. The same did not apply to the group of children with recurrent infection but no other detectable laboratory abnormalities [77] . No association between FCN2 polymorphisms and disease susceptibility [78] was found in the UK invasive pneumococcal disease cohort previously studied for MBL deficiency association [2] .…”
Section: Molecular and Clinical Comparisons Between Ficolins And Mblmentioning
confidence: 94%
“…In a cohort of Polish children with recurrent respiratory tract infection, a group of patients with underlying atopic disorder were significantly more likely to have L-ficolin levels less than the lower range seen in healthy controls. The same did not apply to the group of children with recurrent infection but no other detectable laboratory abnormalities [77] . No association between FCN2 polymorphisms and disease susceptibility [78] was found in the UK invasive pneumococcal disease cohort previously studied for MBL deficiency association [2] .…”
Section: Molecular and Clinical Comparisons Between Ficolins And Mblmentioning
confidence: 94%
“…In recent years, the association between genetic variations in MBL2 , and to a lesser extent FCN2 , and susceptibility to disease have been the subject of various studies 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31. An association between MBL2 polymorphisms and clinical outcome has been described in children with recurrent infections22 and in adult patients with meningococcal sepsis 17…”
Section: Introductionmentioning
confidence: 99%
“…An association between MBL2 polymorphisms and clinical outcome has been described in children with recurrent infections22 and in adult patients with meningococcal sepsis 1729 Behçet's disease,20 peritonitis in patients undergoing peritoneal dialysis28 and recurrent respiratory infections in children 16, 18. More recently, the role of MBL2 polymorphisms in invasive pneumococcal disease25, 27, 30, 31 and CAP23, 24 has been studied but with conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…A few recent studies have revealed that a low concentration of L-ficolin correlated with recurrent respiratory infections in childhood [131], but there is no data regarding the serum concentrations of L-ficolin in maintenance HD patients. In collaboration with Inoshita et al [132], we performed a study on complement deficiencies screened by measurement of functional activities of the three complement pathways in HD patients.…”
Section: Peritoneal Dialysis: Animal Model and Patientsmentioning
confidence: 99%